Dance Video Development Tutorial Betaja Dayak Kancing’k Meliau District for Art Culture Learning in Junior High School - Sesilia Wynni Wilhimina Tanema; Aloysius Mering; Indri Astuti (STKIP Singkawang, 2023)
The purpose of this study was to develop a video tutorial for the Betaja Dayak Kancing’k dance in the Meliau sub-district for learning Cultural Arts in Junior High School. To achieve the research objectives, the Research and Development (R&D) method of the ADDIE development model was used. With the ADDIE Development model, the research is carried out through the stages of (1) Analyze, (2) Design, (3) Develop, (4) Implement, and (5) Evaluate. This research was conducted at SMP Brother Pontianak 9th grade with 30 students and four validators, design experts, media experts, and dance learning materials experts. Data from expert instruments with qualitative and quantitative analysis as a whole from the results of data analysis (in the range of values 1-5) The tutorial video design was declared